2016
DOI: 10.5815/ijitcs.2016.05.07
|View full text |Cite
|
Sign up to set email alerts
|

ICT Definition Implication on ICT Career Choice and Exclusion among Women

Abstract: ICT is driving all areas of the economy and is likely to dictate the future for all genders. The narrow definition of ICT has greatly impacted on the female gender choosing ICT as a career of choice. There are few women in the ICT careers. The study sought to determine the nature of ICT career gender exclusion, status and trend of ICT job opportunities, source of ICT gender career exclusion and the contribution of the narrow definition to the exclusion. A mixed method of survey and desktop method was employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Career choices are made by young people during their early secondary school career [27]. This is a similar assertion made by Armstrong and Riemenschneider [4] who examined an earlier model by scholar Ahuja [2], which noted that the choice of a career in IT is made years before the individual starts working.…”
Section: Literature Reviewsupporting
confidence: 59%
“…Career choices are made by young people during their early secondary school career [27]. This is a similar assertion made by Armstrong and Riemenschneider [4] who examined an earlier model by scholar Ahuja [2], which noted that the choice of a career in IT is made years before the individual starts working.…”
Section: Literature Reviewsupporting
confidence: 59%
“…Current estimates show that most ICT workers have either earned their degrees from a university or vocational education and training institutions in Africa. Many important factors fuel the growth and supply of skilled ICT employees on the continent, including graduate-level job prospects, a well-defined career roadmap to guide career aspirations, and an employer-friendly environment that promotes employability [ [2] , [3] , [4] ].…”
Section: Introductionmentioning
confidence: 99%
“…• male dominated (Allen et al, 2007;Haraway, 1997;Kutanis & Bayraaktaroglu, 2003;Wajcman, 2010), as revealed in the masculine terms (Wajcman, 2004) used to describe this field, such as, "boys club" or "man's world" (Sekeleni, 2014) • marked by gender differences in occupations (Dlamini, 2012;Sekeleni, 2014;Women in IT Scorecard, 2015), as evidenced by women's declining representation (Kvochko, 2016;Lewis et al, 2007;Webb & Young, 2005), especially in key ICT decision-making environments (Mamabolo, 2016), where women find it difficult to break the "glass ceiling" (Cape Times, 2015) • characterised by a conspicuous widening of the digital divide in ICT skills and usage between males and females (Douglas, 2016;World Economic Forum, 2013), which can be attributed to historic structural inequalities in the education system (across all levels), where girls or women, from both developed (Interface 3, 2015) and developing nations (Njoki et al, 2016;OFSTED, 2009;Whyte, 2010) still have limited access to ICT education • notable for the marked differences in the "horizontal" and "vertical" employment of males and females (Bettio & Verashchagina, 2009;Ghoshal & Passerini, 2006;Al Sebaie, 2015), which is ascribed to the glaring gaps in the ICT skills of males and females (MICT SETA, 2014) as reported in a recent ICT skills survey (Schofield, 2016); • characterised by patriarchal (Haraway, 1997;Paasonen 2005) and cultural (Teoh & Chong, 2014;Sekeleni, 2014) predispositions that encourage women's subordination within the sector in terms of their role and contribution (McQuillan, 2009;Minniti, 2010), which is often regarded as being of less significance (Ahl, 2006) compared to that of their male counterparts -a supposition rooted in a c...…”
Section: Introductionmentioning
confidence: 99%